2019
DOI: 10.1016/j.geoforum.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

From sustainable to smart: Re-branding or re-assembling urban energy infrastructure?

Abstract: Visions of sustainable cities have increasingly been substituted by the ambition to become a 'smart city' in recent years. Ongoing scholarly discussions often focus on how sustainability and 'smartness' relate to each other conceptually, to which extent smart city technologies contribute to making cities more sustainable, and calls to prioritise social issues over technology. The questions of how this 'shift to smart' has unfolded, and how it has reshaped strategies and interventions to make cities and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 34 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…He concluded that “the technological dimension is totally superimposable upon the global dimension; in fact, all current global cities are also smart cities, but the technological character of these cities has not yet acquired a full global dimension” (p. 774) Borsekova et al (2018) have discovered the size of cities matters in smart city rankings in Europe. Parks and Rohracher (2019, p. 51) have pointed out the focus on sustainability in smart city discourses by noting “… even when smart city discourses are appropriated by actors in existing sustainable city assemblages, the discursive shift might eventually allow smart city assemblages to colonize existing institutions and socio-material practices. But the shift does not take place through explicit controversy between two discourse coalitions and it therefore remains important to further investigate the conditions that allow for a change in dynamics from appropriation to colonization.”…”
Section: The Evolution Of Cities From Being Ordinary To Being Smartmentioning
confidence: 99%
“…He concluded that “the technological dimension is totally superimposable upon the global dimension; in fact, all current global cities are also smart cities, but the technological character of these cities has not yet acquired a full global dimension” (p. 774) Borsekova et al (2018) have discovered the size of cities matters in smart city rankings in Europe. Parks and Rohracher (2019, p. 51) have pointed out the focus on sustainability in smart city discourses by noting “… even when smart city discourses are appropriated by actors in existing sustainable city assemblages, the discursive shift might eventually allow smart city assemblages to colonize existing institutions and socio-material practices. But the shift does not take place through explicit controversy between two discourse coalitions and it therefore remains important to further investigate the conditions that allow for a change in dynamics from appropriation to colonization.”…”
Section: The Evolution Of Cities From Being Ordinary To Being Smartmentioning
confidence: 99%
“…The second element of territorialisation that we leverage to analyse City Brain as an experimental urban platform is drawn from studies of architecture and urban design that point to the physical, geographically-specific elements of territorialisation processes (Kärrholm 2012 ), and to the importance of the local context as a way of negotiating smart and platform city products and policies that may, under close inspection, display significant local diversity, as shown in studies of the territorialisation of smart city discourses and strategies in the UK (Caprotti and Cowley 2019 ). Based on this, we aim to show how cities that develop smart and urban platform projects ‘might become home to assemblages whose constitutive parts are homogeneously drawn from a smart city repertoire made up of discourses and material elements’ (Parks and Rohracher 2019 , p 53), whilst these self-same elements and discourses become locally-determined through geographical contingency. In the case of City Brain, the set of global smart city discourses in which Alibaba’s agency can be situated are translated into a contingent context specific to Hangzhou—and, eventually, to other cities in China and internationally that have adopted the City Brain platform.…”
Section: Platforming and Experimenting With The Chinese Smart Citymentioning
confidence: 99%
“…The government is entirely behind that, supporting festivals such as SXSW and Austin City Limits and having a division that focuses specifically on nurturing the music industry. That means that being an Austin musician carries cachet, as does being an Austin resident in general, which means that the locals are actively participating in the positive positioning of their city simply by enjoying their quality of life.Efforts at city branding practice have followed a somewhat linear trajectory over time, ranging from creating logos and catchy slogans (Anholt 2005), cultural flagship projects (Vivant 2011; Ulldemolins 2014), architectural edifices (Holliday 2009; Ren 2008), event spectacles such as Olympic games (Zhang and Zhao 2009; Smith 2005), food festivals (Blichfeldt and Halkier 2014) to gearing toward more recent urban greening policies (Shing, Peters, and Marafa 2015; Andersson 2016), social diversity (Hassen and Giovanardi 2018), and smart city profiles (Parks and Rohracher 2019). Among these strategies that speak to the taste of city leaders, cultural projects exhibit a rising trend, where the use of culture as the cornerstone of branding strategies is frequently metamorphosed into monumental structures.…”
Section: City Branding: An Overviewmentioning
confidence: 99%